An Analysis of Learning and Study Strategies Among Undergraduate Students - Iskandarsyah; Ardian, Riski; Arisman, Ahmad (SATKRIYA : Jurnal Pengabdian Kepada Masyarakat, 2023)
The study aimed to assess learning and study strategies among undergraduate students and explore variations based on achievement level, academic year, college type, and gender. It employed a descriptive analytical approach with 426 participants using the Learning and Study Strategies Scale - third version (LASSI-3) to measure strategies. Means and standard deviations were computed, and dependent multivariate analysis of variance (MANOVA) and analysis of variance (ANOVA) were utilized for analysis. Results indicated medium to high prevalence of strategies, with significant differences in strategies across achievement levels favoring high achievers. Graduates exhibited varied strategies in Motivation and Test Strategies by academic year. Scientific college students differed significantly in Anxiety, Concentration, Motivation, Selecting Main Ideas, and Test strategies. Gender did not yield significant differences in strategies. Recommendations include educating students on the importance of learning strategies, emphasizing self-regulation skills, and training educators and parents in effective teaching strategies.